Influence of cocamidopropyl betaine on the formation and carbonation of portlandite – A microscopy study. (28th February 2018) - Müller, Torsten; Krämer, Christina; Pritzel, Christian; Bornemann, Rainer; Kowald, Torsten L.; Trettin, Reinhard H.F.; Bolívar, Peter Haring
Abstract: In this study, the influence of concentrated cocamidopropyl betaine (TEGO® Betain F50) on the formation of calcium hydroxide and its carbonation is shown. Investigations to improve the comprehension of the impact on the morphologies and course of carbonation in the presence of the surfactant have been carried out, using several microscopic methods. In situ light microscopy was used to follow the carbonation reaction step by step. To get a closer view to the appearance of reaction products, fluorescence microscopy and electron microscopy has been applied. With the help of micro Raman spectroscopy adsorbed surfactant on the surface of portlandite crystals could be located. This work has been done to get a better understanding of the observations made in previous studies in the context of foam concrete and its optimization, using cocamidopropyl betaine as foaming agent.